2018
DOI: 10.1080/87565641.2017.1334782
|View full text |Cite
|
Sign up to set email alerts
|

Applying a Cognitive Neuroscience Perspective to Disruptive Behavior Disorders: Implications for Schools

Abstract: A cognitive neuroscience perspective seeks to understand behavior, in this case disruptive behavior disorders (DBD), in terms of dysfunction in cognitive processes underpinned by neural processes. While this type of approach has clear implications for clinical mental health practice, it also has implications for school-based assessment and intervention with children and adolescents who have disruptive behavior and aggression. This review articulates a cognitive neuroscience account of DBD by discussing the neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 185 publications
0
7
0
1
Order By: Relevance
“…Callous-unemotional traits (i.e., lack of empathy, guilt, restricted interpersonal sensitivity, and a lack of concern for performance) delineate an important subgroup of antisocial children (Waller et al, 2020a ) who show an earlier onset and more severe, varied, and persistent forms of antisocial behavior (McMahon et al, 2010 ). However, very few studies have explored callous-unemotional traits in relation to school engagement or academic outcomes, despite clear potential implications for school-based interventions that could disrupt risky pathways to antisocial behavior (Tyler et al, 2019 ). This study addresses this gap by investigating the influence of callous-unemotional traits and antisocial behavior on trajectories of academic grades and school engagement in South Korean children over an academic year.…”
Section: Introductionmentioning
confidence: 99%
“…Callous-unemotional traits (i.e., lack of empathy, guilt, restricted interpersonal sensitivity, and a lack of concern for performance) delineate an important subgroup of antisocial children (Waller et al, 2020a ) who show an earlier onset and more severe, varied, and persistent forms of antisocial behavior (McMahon et al, 2010 ). However, very few studies have explored callous-unemotional traits in relation to school engagement or academic outcomes, despite clear potential implications for school-based interventions that could disrupt risky pathways to antisocial behavior (Tyler et al, 2019 ). This study addresses this gap by investigating the influence of callous-unemotional traits and antisocial behavior on trajectories of academic grades and school engagement in South Korean children over an academic year.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, theoretical models of CD etiology have proposed that dysfunction in different neurocognitive systems may be associated with different types of CD-related symptom sets (11), including CU traits [for a recent review, see (12)]. Accumulating evidence indicates that children with CD but low levels of CU traits typically show a heightened affective reactivity to perceived negative emotional stimuli, such as angry or ambiguous neutral facial expressions, which may be regarded as social threat or provocation, resulting in reactive aggressive acts (13).…”
Section: Introductionmentioning
confidence: 99%
“…To date, the bulk of research on CU traits and their influence on social interaction has focused on parenting, leading to calls for greater attention to CU traits in the school context to help guide school-based interventions (Tyler et al 2019 ). In terms of the differential impact of punishment versus reward-based parenting practices on CU traits, early studies suggested that harsh parental discipline predicted more severe antisocial behavior among children with low, but not high, levels of CU traits (i.e., a significant moderation effect), suggesting that children with high CU traits may be less sensitive to parental discipline (Hipwell et al 2007 ; Oxford et al 2003 ).…”
mentioning
confidence: 99%